Influence of weather factors on light-trap catches of groundnut leafminer (Aproaerema modicella) (Lepidoptera: Gelechiidae) - BASKARAN, R K MURALI; MAHADEVAN, N R (The Indian Journal of Agricultural Sciences, 2013)
The relationship between weather factors and light-trap catches of leafminer (Aproaerema modicella Deventer) of groundnut (Arachis hypogaeo L.) was studied during 1987, 1988 and 1989 at Vridhachalam. The number of moths attracted to light-trap was significantly high in second fortnight of August andSeptember in 1987 (11 peak catches). in first fortnight of October in 1989 (7 catches) and in March and first fortnight of April 1988 (6 catches). Pooled analysis of data revealed thatÂ  the light-trap catches had a negative association with maximum temperature (r = -0.18). minimum temperature (r = -0.01) Â  and sunshine hours (r = -0.18), and a positive association with relative humidity (r = 0.24) and rainfall (r = -0.41). The correlation studies indicated that rainfall alone exerted a significant positive influence, and an increase of 1 mm rainfall would increase the leafminer adults by 8.9.